Upwind and High-Resolution Methods for Compressible Flow: From Donor Cell to Residual-Distribution Schemes (Communications in Computational Physics, 2018)
In this paper I review three key topics in CFD that have kept researchersbusy for half a century. First, the concept of upwind differencing, evident for 1-Dlinear advection. Second, its implementation for nonlinear systems in the form of high-resolutionschemes, now regarded as classical. Third, its genuinely multidimensionalimplementation in the form of residual-distribution schemes, the most recent addition.This lecture focuses on historical developments; it is not intended as a technical reviewof methods, hence the lack of formulas and absence of figures.